[RETRACTED] Corporate governance, capital structure, and performance in family and non-family firms - Tyara Dwi Putri; Purbo Jadmiko; Neva Novianti; Giralda Triyani Arista (Diponegoro International Journal of Business, 2022)
This article was retracted due to the following reasons. A retraction announcement will be made in Vol 6 (1), 2023. RETRACTION TO:Putri, T. D., Jadmiko, P., Novianti, N., & Arista, G. T. (2022). Corporate governance, capital structure, and performance in family and non-family firms. Diponegoro International Journal of Business, 5(1), 24-32. https://doi.org/10.14710/dijb.5.1.2022.24-32This article has been retracted by Publisher based on the following reason:Letter to Editor from Dr. Dedi Iskamto (Managing Editor of ADPEBI International Journal of Business and Social Science/AIJBS) reported that he found a dual publication for this paper with the paper that was also published in AIJBS Vol. 2 (1), 2022. After a careful review, we found that the papers have a very significant similarity. Even the data and analysis are exactly the same. We then sent a letter to the corresponding author and the editor of AIJBS asking for clarification. Based on our correspondence with the corresponding author, she admitted that prior to the submission to our journal, they already made a submission to the AIJBS, but she argued that she had withdrawn the submission before submitting it to our journal. However, our communication with the editor of AIJBS made it clear that the author never formally requested withdrawal. Even after the editor sent the acceptance letter, the editor never received a withdrawal, so they assumed that the author agreed to process the publication. Furthermore, when we asked the author to send proof of withdrawal prior to submission to our journal, she failed to provide sufficient evidence.Based on the communication with the corresponding author and the editor of AIJBS, we conclude that the authors made misconduct, particularly by creating a double submission. The academic community takes this kind of misconduct as a very serious issue. Furthermore, it is clearly mentioned in our author guidelines that "DIJB cannot accept an article if it is not the author's original work, has been published before (a conference paper could be accepted if it has been revised so that it is significantly different), or is currently under consideration for publication in another journal." Therefore, we decided to retract this paper.Apologies are offered to readers of the journal that this was not detected during the submission process. We have conducted careful measures to minimize this misconduct happened by doing a plagiarism screening using Google-based search engines after receiving a submission. However, since we received the paper before it has been published in AIJBS, this made us difficult to detect this misconduct.